Jamie's Fifteen (15) Minute Meals - Oliver, Jamie (London Penguin Books Ltd., 2012)
Designed to excite and inspire people to prepare a balanced, nutritional, no-nonsense meal every night of the week, this book covers homely British dishes, Mediterranean family staples as well as Thai, Chinese and Indian-inspired dishes.
Include Color Illustrations and Index.
Delicious, Nutritious, Super-Fast Food.
Keywords: Quick and easy cooking -- Cooking